2015
DOI: 10.1007/s12678-015-0269-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Addition of Ru and/or Fe in the Stability of PtMo/C Electrocatalysts in Proton Exchange Membrane Fuel Cells

Abstract: In this work, the activity, stability, and CO tolerance of ternary and quaternary electrocatalysts formed by PtMo/C-PtFe/C, PtMo/C-PtRu/C, and PtMo/C-PtRuCPtFe/C were studied in the anodes of proton exchange membrane fuel cells (PEMFCs). Cyclic voltammetry (CV) was used to study the surface characteristics and stability of the electrocatalysts and polarization curves were used to investigate the performance of PEMFC anodes supplied with pure hydrogen and hydrogen containing 100 ppm CO. Online mass spectrometry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 33 publications
(37 reference statements)
1
12
0
1
Order By: Relevance
“…PtMo supported (20 wt.%) on Vulcan XC-72R (Cabot, previously heat-treated as described above) was prepared following a previously described preparation procedure. [10][11][12] The method is essentially the same as that used for incorporation of Pt on MoO 2 …”
Section: Preparation Of the Electrocatalystsmentioning
confidence: 99%
See 3 more Smart Citations
“…PtMo supported (20 wt.%) on Vulcan XC-72R (Cabot, previously heat-treated as described above) was prepared following a previously described preparation procedure. [10][11][12] The method is essentially the same as that used for incorporation of Pt on MoO 2 …”
Section: Preparation Of the Electrocatalystsmentioning
confidence: 99%
“…The materials and method for the preparation of MEA and its components are described in details elsewhere. [8][9][10][11][12][22][23][24] The gas diffusion layer comprised a mixture of carbon powder (Vulcan XC-72, Cabot) with 15 wt.% of polytetrafluoroethylene (PTFE, TE 3893, DuPont) placed on both sides of the carbon cloth substrate (Panex 30, Zoltek), each with a carbon + PTFE load of 3 mg cm -2 . The catalyst layer was deposited on one of the faces of the diffusion layers using a homogeneous suspension formed by appropriated amounts of Nafion ® (Aldrich, 5 wt.%) or Aquivion ® (D9825BS, Aldrich, diluted to 5 wt.% in water), the electrocatalysts (PtMo/C, Pt/MoO 2 -C, and Pt/C) and isopropanol.…”
Section: Electrochemical Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nowadays, it is generally accepted that the association between Pt and a second metal improves the electrocatalytic activity, because it allows the catalyst to perform the oxidative removal of adsorbed CO. Also, these bimetallic catalysts have further been modified either with a third or fourth element for the purpose of improvements in the activity and stability. More recently, it has been found that the addition of Ru and/or Fe to the PtMo/C catalyst leads to an improvement in the activity towards H 2 oxidation in the presence of CO as well as in the stability of the resultant catalysts (Hassan et al 2014c). In subsequent work it has been shown that the addition of Au nanopartilces to the lattice of PtRu catalyst causes a decrease in the onset potential for methanol oxidation in addition to the gain in stability up to 10,000 voltammetric cycles.…”
Section: Introductionmentioning
confidence: 99%